The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1039/c6ce00900j
|View full text |Cite
|
Sign up to set email alerts
|

Metal–organic and supramolecular lead(ii) networks assembled from isomeric nicotinoylhydrazone blocks: the effects of ligand geometry and counter-ion on topology and supramolecular assembly

Abstract: A new series of six structurally diverse leadIJII) coordination compounds was assembled from two isomeric nicotinoylhydrazones as neutral ligands and three PbIJII) salts with different monoanions (chloride, nitrate and thiocyanate) as starting materials. The products were isolated in good yields and were fully characterized, including by single-crystal X-ray diffraction and theoretical methods. Within the six compounds, three feature 2D metal-organic networks, two are 1D coordination polymers, and another one co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 83 publications
2
23
0
Order By: Relevance
“…The Pb 2+ ion exhibits six‐coordinate configuration defined by two μ 2 ‐Cl – ions and four carboxylic oxygen atoms that come from one chelating acetic acid and one ligand L 2 . The bond lengths of Pb‐Cl are 2.7708(15) Å and 3.121(3) Å, and the bond lengths of Pb–O are changing from 2.379(5) to 2.736(5) Å, which are comparable to those of the reported Pb‐based coordination polymers . Six‐connected Pb 2+ and its symmetry generated counterparts are linked together by μ 2 ‐Cl – and μ 2 ‐CH 3 COO – from ligand L 2 to generate an infinite “PbCl(CH 3 COO)” chain extending along [0 1 0] direction.…”
Section: Resultssupporting
confidence: 54%
“…The Pb 2+ ion exhibits six‐coordinate configuration defined by two μ 2 ‐Cl – ions and four carboxylic oxygen atoms that come from one chelating acetic acid and one ligand L 2 . The bond lengths of Pb‐Cl are 2.7708(15) Å and 3.121(3) Å, and the bond lengths of Pb–O are changing from 2.379(5) to 2.736(5) Å, which are comparable to those of the reported Pb‐based coordination polymers . Six‐connected Pb 2+ and its symmetry generated counterparts are linked together by μ 2 ‐Cl – and μ 2 ‐CH 3 COO – from ligand L 2 to generate an infinite “PbCl(CH 3 COO)” chain extending along [0 1 0] direction.…”
Section: Resultssupporting
confidence: 54%
“…[25,26,38,98,99] Previous studies have confirmed the trend that the tetrel bond grows stronger as T becomes larger, [30,32,33,47,100] but that the effect levels off between Sn and Pb. However, there are a few works dealing with tetravalent Sn and Pb, and the noncovalent bonds they form with various bases.…”
Section: Discussionmentioning
confidence: 82%
“…However, there are a few works dealing with tetravalent Sn and Pb, and the noncovalent bonds they form with various bases. [25,26,38,98,99] Previous studies have confirmed the trend that the tetrel bond grows stronger as T becomes larger, [30,32,33,47,100] but that the effect levels off between Sn and Pb. [45,101] An earlier work [45,102] supports the result noted here that the deformation energy induced within the Lewis acid molecule by formation of a tetrel bonded complex drops as the central tetrel atom grows in size.…”
Section: Discussionmentioning
confidence: 82%
“…The term "tetrel bond" was first coined in 2013 17 where it was related to atoms below C in this family of the periodic table. And indeed it is to these heavier atoms that most previous work has been devoted [18][19][20][21][22][23][24][25][26] . In the case of the C atom, its ability to engage in a TB has typically been amplified by adding a number of electron-withdrawing substituents like F [27][28][29] rather than considering a CH3 group itself.…”
Section: Introductionmentioning
confidence: 99%